Controle do carrapato-do-boi de forma sustentável: sensibilidade, fatores econômicos e sistema Lone Tick - Jacqueline Cavalcante Barros (2024)
The international market is signaling a potential increase in demand for animal protein over the next decade, creating an opportunity for Brazil to increase its beef exports by 29.7%. To meet this demand, productivity in the cattle production chain must be increased. This fact makes investment in genetics a strategic point in this process, since the racial composition of cattle in the country has only 15% of Bos taurus breeds and their crossbreeds, B. taurus breeds, are more productive and more sensitive to the Rhipicephalus microplus tick. Regardless of the technological level, the level of tick infestation directly affects the economic and productive performance of the different livestock production systems in Brazil. With the intention of providing information to increase productivity and mitigate environmental impacts in the production sector, the present study had the following objectives: to develop a practice for tick R. microplus control, without the use of acaricides, through a rotational management system; to evaluate the sensitivity of cattle breeds in relation to ticks to better understand the risks of high infestations of this parasite; to analyze the economic impact of tick infestations in the cattle production chain; and to validate the Lone Tick System with a focus on sustainable development.The study resulted in the preparation of four articles: the first article deals with the development of a rotational management system called the Lone Tick System, which controlled the level of tick infestation in the Senepol breed without the use of acaricides for one year in the Cerrado, and maintained the enzootic balance for TPB. The second article presents the Tick Ruler, a simple and easy-to-understand tool, which allows producers and technicians to have an overview of the racial composition of cattle and their sensitivity to ticks, which can be fundamental in decision-making to find a balance between increased productivity and the risk of economic losses depending on the breed. The third article discusses the increased sensitivity to ticks as a result of the migration to higher-productivity breeds, the economic impact on the production sector, tick resistance to acaricides, and the need for appropriate public policies and new technologies to mitigate the use of chemical products. The fourth article presents a case study using the Lone Tick system in the Pampa biome, with an evaluation of efficiency and economic viability. The results show the system's ability to reduce the number of ticks per animal below the economic threshold, promoting enzootic stability for TPB, reducing the number of acaricide applications by more than 90%, increasing productivity, reducing operating costs by 64.4%, with a profit margin of 70%, a benefit/cost ratio of 1.79, and profitability of 2.71%. With these results, the Lone Tick system has the potential to serve a growing market niche that seeks agroecological production as an alternative, while also preserving biodiversity with sustainable extensive production. Sustainable livestock farming that promotes economic growth with social development, preserving biodiversity and responsibly managing the use of natural resources for future generations is possible.